Saints and monsters in Medieval French and Occitan literature : sublime and abject bodies - Grange, Huw (Research monographs in French studies, 2017)
From rubbery martyrs to wraith-like ascetics, and from pestilential dragons to troublesome giants, the bodies that fascinated audiences of saints' lives during the Middle Ages increasingly inform theoretical debates in medieval studies concerning corporeality. Saints and Monsters draws on notions of the 'sublime' and the 'abject' to explore the role played by these holy and unholy bodies in community formation. Examining a series of biographies of Sts Margaret, George, Honorat and Enimia - some of them previously unknown to scholarship - Huw Grange argues that the extraordinary bodies of medieval French and Occitan hagiography mutate in relation to a range of shifting historical, cultural and geographical imperatives.